Analisis Faktor-Faktor Masyarakat Lebih Memilih Investasi Dalam Deposito Dari Pada Produk Investasi Lain - Setyantoro, Delly Isnatani Dalove; Sudaryanti, Dwiyani; Anwar, Siti Aminah (Universitas Islam Malang, 2023)
This study aims to determine the factors of the level of profit sharing, terms, service, security, cost, and location influence the public in choosing to invest in deposits over other investment products. This research is a quantitative research approach. Collecting data in this study using a questionnaire method (questionnaire). The data analysis method used in this study uses the factor analysis method with Validity Test, Reliability Test, Classical Assumption Test, Mukticolionarity Test, Heteroscedasticity Test, Normality Test, Descriptive Statistics and Sample t-test. The results of this study indicate that the variables in this study are profit sharing (X1) with a Significance value (Sig) variable. it has a significance value <0.05, which means that this variable influences the decision to invest in deposits. Meanwhile, the service level variable (X3) has a significance value of 0.861, or >0.05, which means that the service level variable (X3) has no effect on the decision to invest in deposits rather than investing in others.Keywords: Deposits , Community factors, Investment.